Comparison of Irbesartan Microbial Transformation Processes in Pure Cultures and Consortia - Gradl, Anna (Jihočeská univerzita, 2021)
Pharmaceutical contamination of the environment affects living organism and poses risks for human health. Bioremediation is possible through various soil microorganisms. This thesis studies the removal of the pharmaceutical irbesartan by four bacterial strains, three fungal strains, and seven different consortia and identifies the obtained transformation products of irbesartan.
Comparison of Irbesartan Microbial Transformation Processes in Pure Cultures and Consortia
Keywords: irbesartan; biotransformation; emerging pollutants; pharmaceutical contamination; soil microcosms; irbesartan; biotransformation; emerging pollutants; pharmaceutical contamination; soil microcosms